The nrfA-type microbial communities are widespread in hot springs of the Tibet-Yunnan geothermal zone - Chen, Xi; Wu, Geng; Yu, Zhicheng; Li, Fangming; Jiang, Hongchen (Frontiers in Microbiology, 2025)
The microorganisms are main drivers of biogeochemical processes in geothermal ecosystems. The dissimilatory nitrate-to-ammonium reduction pathway (DNRA) could act as an alternative source of ammonium and provide an important nitrogen supply for the maintenance of geothermal ecosystems. Investigating the distribution of DNRA-functional bacteria is of great significance to understanding the source of biological nitrogen production in geothermal environments. In this study, we characterized the community distribution of microorganisms harboring nrfA genes in the sediments of hot springs from the Tibet-Yunnan geothermal zone, with the use of Illumina MiSeq high-throughput sequencing of nrfA genes and R language software for statistical analysis. In the present study, the nrfA genes were successfully amplified from the hot springs with a temperature of 38°C–80°C. The nrfA-based phylogenetic analysis showed that the DNRA pathway is widespread within the geothermal ecosystems, with microorganisms harboring nrfA genes predominantly belonging to phyla Chloroflexi, Proteobacteria, Deinococcus-Thermus (top 10), etc. Genus-level analysis revealed Thermoflexus (Chloroflexi) as the dominant taxon in the DGQ, while Geothrix (Acidobacteria) showed peak abundance in weakly acidic sites. The DNRA-functional community structure and nrfA gene abundance also showed a sample variability, even among samples from the same region, there were differences in dominant populations and overall nrfA gene abundance between them. Statistical analysis results indicate that the distribution of nrfA type microorganisms was mainly influenced by physicochemical factors, including pH, SO42−, and NO2− concentrations. These findings deepen our understanding of the nitrogen cycle in extreme environments and provide valuable perspectives on the role of nitrogen metabolism in both contemporary and ancient geothermal systems.